Reading practices - Fluck, Winfried; Leypoldt, Günter; Löffler, Philipp (REAL, 2015)
Intro -- Contents -- Acknowledgements -- Contributors -- Philipp Löffler: Introduction: Reading in the Age of Academic Literary Studies -- Winfried Fluck: Shadow Aesthetics -- Günter Leypoldt: Acquired Taste (Toni Morrison on Oprah) -- Amy Hungerford: GPS Historicism -- Wendy Griswold and Hannah Wohl: Evangelists of Culture: One Book Programs and the Agents Who Define Literature, Shape Tastes, and Reproduce Regionalism -- Daniel Silliman and Jan Stievermann: Reading the Supernatural in Contemporary American Ethnic and Christian Fiction -- Timothy Aubry: The Discipline of Feeling: The New Critics and the Struggle for Academic Legitimacy -- Merve Emre: Fulbright Love -- Philipp Löffler: Identity Fiction and the Rise of Theory -- Amy L. Blair: "Tasting and Testing Books": Good Housekeeping's Literary Canon for the 1920s and 1930s -- Christa Buschendorf: Reading Shakespeare Matters: Symbolic Struggles over Literary Taste among Black Intellectuals -- Paul B. Armstrong: How Historical is Reading? What Literary Studies Can Learn from Neuroscience (and Vice Versa) -- Dustin Breitenwischer: Reading In-Between: Interpretation as Experience (and the Case of Sylvia Plath's "Soliloquy of the Solipsist") -- Call for Papers for REAL Vol. 33/2017.
Keywords: Aufsatzsammlung; Konferenzschrift -- 2013 -- Heidelberg; Geschichte 1950-2000; Professionalisierung; Lesen; Rezeption; Literaturwissenschaft; USA